Government use of print official publications in the Holy Roman Empire, 1500-1600 - Limbach, Saskia (Studien zur europäischen Rechtsgeschichte, 2021)
Front Cover -- Impressum -- Table of Contents -- Acknowledgements -- Abbreviations and Editorial Conventions -- List of Illustrations -- Introduction -- Book history -- Legal history -- Political culture -- Method and sources -- Outline -- Terminology -- Chapter One: Governing the German Duchy -- The discovery of print -- 'For the common good': ruling Württemberg -- Addressing immediate concerns -- The interplay of ordinances -- 'A humble request': appeals and law-making processes -- To print or not to print: the dissemination of official announcements -- Conclusion -- Chapter Two: The Dukes' Printers -- Printing for the government -- Trial and error in Württemberg -- Hans Wehrlich von Erfurt in Stuttgart (1522-1524) -- Ulrich Morhart - the loyal servant -- Family business. Morhart's legacy -- Obstructive cooperation -- Conclusion -- Chapter Three: Governing the German City -- Cologne -- Proclaiming law and order -- Official publications -- Printing law and order, 1500-1550 -- 'In these dangerous times' - printed ordinances in Cologne 1550-1600 -- Printing ordinances to overcome times of trouble in Antwerp -- The council's limited use of print -- Conclusion -- Chapter Four: The Council's Printers -- Cologne as a print centre -- Printing for municipal governments -- 'Our well-known and trusted printer' - prestigious print orders -- Small print produced in big print shops -- The printing councillor -- Conclusion -- Conclusion -- Intention -- Size of jurisdiction -- Type of government -- Special circumstances -- Local print industry -- Sources and bibliography -- Archival sources -- Early modern printed books not listed in the appendix -- Edited primary sources -- Internet sources -- Works of reference -- Unpublished work -- Appendix -- Württemberg -- Cologne -- Index.